Two new species of Indonemoura (Plecoptera: Nemouridae) from China - Li, Weihai; Yang, Ding; Sivec, Ignac (Zootaxa, 2005)
Indonemoura guangxiensis Li and Yang, sp. nov. and Indonemoura trispina Li and Sivec, sp. nov., of the family Nemouridae, are described from China. Their relationships to other species in the genus are discussed.